CATTLE REPRODUCTIVE PARAMETERS IN THE LIMA DAIRY REGION - Ortiz A., Dante (2009)
The age at first service (EPS), age at first calving (EPP), calving – first service interval (IPPS), calving – conception interval (IPC), inter-calving interval (IEP), number of services per conception (NSC), conception rate at first service (TCPS) and overall conception rate (TCG) were determined from historical data of 559 dairy cows from 4 intensive milk dairy farms in the Lima region. Variables under analysis were farm, calving season (summer: December–March; winter: April–August; spring: September–November) and parity (primmiparous; multiparous). EPS was 17.5 ± 0.1 months (n = 559), EPP was 27.2 ± 0.2 months (n = 455), IPPS was 109.2 ± 1.5 days (n = 1233), IPC was 181.1 ± 3.4 days (n = 1035), IEP was 15.2 ± 0.1 months (n = 775), NSC was 2.41, TCPS was 46.1% (66.9 and 36.5% en heifers and cows, respectively) and TCG was 41.5%. IPPS of cows that calved in winter was statistically shorter that for cows calving in spring and summer (105.0 vs. 112.7 and 113.8 days, respectively). Likewise, multiparous cows showed better reproductive performance than primmiparous cows.